2016
DOI: 10.1080/00223980.2016.1207591
|View full text |Cite
|
Sign up to set email alerts
|

Mediationg Role of Mindfulness as a Trait Between Attachment Styles and Depressive Symptoms

Abstract: Attachment styles and dysfunctional symptoms have been associated. This relationship could be affected by metacognitive capacity. The aim of this study is to clarify the relationship between depressive symptoms, attachment styles, and metacognitive capacity. In addition, the mediating role of metacognition between attachment and depressive symptoms has been studied. A total of 505 participants recruited from the general population of the province of Bizkaia (Spain) completed questionnaires regarding depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
1
7
0
1
Order By: Relevance
“…Good mindfulness abilities have been found to be a protective factor by decreasing the effects of stressors, increasing problem‐solving abilities, and having cognitive flexibility that allows for reducing rumination, over‐generalization, and self‐critical evaluation (Luca, 2019; Shapero et al, 2018; Williston et al, 2020). Linares et al (2016) reported that metacognition abilities and mindfulness levels were associated with depression, and mindfulness had a partial mediator role in the association between attachment style and depression. Linares et al (2016) reported that metacognitive and mindfulness‐oriented therapies could be beneficial for improving depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good mindfulness abilities have been found to be a protective factor by decreasing the effects of stressors, increasing problem‐solving abilities, and having cognitive flexibility that allows for reducing rumination, over‐generalization, and self‐critical evaluation (Luca, 2019; Shapero et al, 2018; Williston et al, 2020). Linares et al (2016) reported that metacognition abilities and mindfulness levels were associated with depression, and mindfulness had a partial mediator role in the association between attachment style and depression. Linares et al (2016) reported that metacognitive and mindfulness‐oriented therapies could be beneficial for improving depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Linares et al (2016) reported that metacognition abilities and mindfulness levels were associated with depression, and mindfulness had a partial mediator role in the association between attachment style and depression. Linares et al (2016) reported that metacognitive and mindfulness-oriented therapies could be beneficial for improving depressive symptoms. In light of these data, it can be suggested that, due to the possible associations highlighted in our research, similar therapies may also be beneficial in improving depressive symptoms in individuals under quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are several published studies concerned with understanding the relationship between attachment and psychopathological symptoms. Although each study has its own methodology, several have pointed out that could be a mediating role of other variables in the relationship between insecure attachment and depressive symptoms in last decades (Kamkar et al, 2012;Linares et al, 2016;Surcinelli et al, 2010) studied mediating role personality traits in the relationship between adult attachment styles and psychological disease. Moreover, in a study conducted in Turkey, analysis of the relationship between anxious attachment, depressive symptoms, OCD symptomology, and social anxiety showed that conscious flexibility -the ability to modify necessary information to produce reactions -plays both partial and complete mediating roles in controlling behaviors (Dağ & Gülüm, 2013).…”
Section: Attachment Causality Orientations and Depressive Symptomsmentioning
confidence: 99%
“…These styles are divided into three categories: Secure, avoidant, and ambivalent (9)(10)(11). Avoidant and ambivalent attachment has a positive relationship with various indicators of psychological distress, including depression and anxiety, negative mood, and psychological distress (12). In addition to a linear and direct relationship between attachment and psychopathology, researchers have tried to identify factors that indirectly affected this relationship.…”
Section: Introductionmentioning
confidence: 99%